Cryopreservation of Dama. Dama (Fallow Deer) Semen using Tris Extender Treated with Soya Milk and Omega3 - Ali A.Z. Al-Saadoun; Hadi Awaad Hesoon; MSc. Haider F.M. Khashan (Indian Journal of Forensic Medicine & Toxicology, 2021)
The experiment was conducted in the Agricultural research’s station due to the College of Agriculture/Al-Muthanna University in the south of Iraq, to study the effect of adding soybean milk and omega3 tothe tris extender on the quality of Dama.Dama (D.Dama) Gazelle semen under cryopreservation- thawingconditions. The semen was collected from four adults males of D.Dama Gazelle using electric ejaculatorsystem .The experiment was contains four treatments :the control treatment using the traditional tris extenderonly , T1.adding 5% soybeans to the tris extender , T2.adding 2% omega3 to the tris extender, T3. Adding5% soybeans + 2% omega3 to the tris extender. It was observed highly significant effect(p? 0.01) of adding5% soybean(T1) and adding 5% soybean+ 2% omega3(T3) to the tris extender on the sperm total motility%and progressive motility % associated with highest viability percentage( explained by the percentage of livesperms) and significant superiority in the results of the HOST test was noticed in this two treatments (T1and T3).This results refers to better cryopreservation success of D. dama Gazelle spermatozoa in particularit was associated with a very good results of acrosome integrity in all treatments, this is the first study in Iraqdeals with cryopreservation of D.Dama Gazelle semen, that helps to application of artificial inseminationand ( for the future) to conservation of the genetic resource for this endangered species.